Nutritional Status of Children Aged 6-59 Months Based on Composite Index of Anthropometric Failure - Rizka Pratiwi; Sudiarti, Trini (Jurnal Kesehatan Masyarakat, 2025)
Composite Index Anthropometric Failure (CIAF) is an alternative indicator for assessing nutritional status in children which can identify all children who are malnourished, whether they are stunting, wasting, underweight, wasting and underweight, stunting and underweight, or a combination of all three. The problem of failure to thrive in children aged 6-59 months based on CIAF in Bojongsari District, Depok City, in 2023 is 29,8%. This figure is higher than conventional measurements with single indicators of stunting, wasting, and underweight in Depok City based on the 2023 SKI, respectively, namely 14.3%, 5.8%, and 12.8%. The research aims to determine the determinants of the nutritional status of children aged 6-59 months based on CIAF in Bojongsari District, Depok City, West Java Province in 2023. This quantitative research with a cross-sectional study design used secondary data, and data analysis was conducted using the Chi-square test and multiple logistic regression. There were 317 children aged 6-59 months in this study. Bivariate analysis showed that variables related to children’s nutritional status based on CIAF were energy intake, protein intake, fat intake, and carbohydrate intake. Multivariate analysis shows that energy intake is the risk factor in children’s nutritional status based on CIAF in children aged 6-59 months in Bojongsari District, Depok City, West Java Province in 2023 after controlling for the variables protein intake and fat intake (p=0.006; OR = 3.493, 95% CI = 1.428 – 8.543).